Low energy ion scattering in He/HOPG system - Bajales Luna, Noelia (2008)
Low energy ion scattering (LEIS) is a unique tool in surface analysis, since it provides the atomic composition of the outer atomic layer, and time of flight ion scattering (TOF) is a non-destructive method of analysis that is sensitive to all elements. The outer surface atoms dominate many processes such as adhesion, electron emission, growth, wetting and overall catalysis. In catalysis, LEIS applications include understanding and improvement of catalytic phenomena, site of poisoning, size of nanoclusters and quantification of promoters. In this work, we study the neutralization of low energy He+ ions on graphite (highly oriented pyrolytic graphite, HOPG) verifying that the ion fraction is close to null, i.e., a large neutralization probability. Resonant neutralization to the ground state (RN) has been the main mechanism expected for He+ scattered by HOPG, but we found that only by including the resonant neutralization to the first excited state (1s, 2s), the small ion fractions measured can be explained. © 2007 Elsevier B.V. All rights reserved.